INTERAKSI SOSIAL DALAM PENGEMBANGAN HUKUM ISLAM PADA MASYARAKAT JAWA DAN BATAK DI PADANGSIDIMPUAN - Kurniawan, Puji (IAIN Padangsidimpuan, 2021)
Padangsidimpuan is a multicultural area because it is inhabited by various religions, cultures, tribes, ethnicities and languages including the Javanese. The Batak people as the majority tribe have different cultures and traditions from the Javanese. Negotiations and cultural adaptation become social interactions of the Javanese and Batak people in Padangsidimpuan. The results of this study indicate that the pattern of harmonious interaction is established through cooperative relationships in the fields of social religion, culture, marriage, politics and socio-economics. The positive impact of social interaction is the creation of social relationships that lead to an integrative relationship pattern, although on the other hand social jealousy sometimes appears due to communication patterns that do not go well and a narrow understanding that gives rise to competition for each tribe.